Optimalisasi Bimbingan Karir dalam Menemukan Minat dan Bakat Bagi Siswa - Febriyanti, Tiara; Setiana, Wiryo; Rahman, Encep Taufik (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2024)
The aim of this research is to determine the effect of self-care guidance on the independence of children with special needs at Al-Biruni Middle School. This research uses a quantitative approach with a simple linear regression method. The self-care guidance variables include self-knowledge skills, environmental cleanliness, art, as well as aspects of independence, namely self-help skills and functional academics. The results of research carried out using a simple linear regression test show a sig value of 0.000 < 0.05, so H1 is accepted and H0 is rejected, which means that there is an influence of self-care guidance on the independence of children with special needs, with an influence level of 0.474, then the influence of self-care guidance on the independence of children with special needs is 0.971 or 94% and the rest is influenced by other variables outside the research. This shows that self-care guidance has a positive influence on the independence of children with special needs.